Effects of manganese doping on the structure evolution of small-sized boron clusters. (25th May 2017) - Zhao, Lingquan; Qu, Xin; Wang, Yanchao; Lv, Jian; Zhang, Lijun; Hu, Ziyu; Gu, Guangrui; Ma, Yanming
Abstract: Atomic doping of clusters is known as an effective approach to stabilize or modify the structures and properties of resulting doped clusters. We herein report the effect of manganese (Mn) doping on the structure evolution of small-sized boron (B) clusters. The global minimum structures of both neutral and charged Mn doped B cluster MnB n Q ( n   =  10–20 and Q   =  0, ±1) have been proposed through extensive first-principles swarm-intelligence based structure searches. It is found that Mn doping has significantly modified the grow behaviors of B clusters, leading to two novel structural transitions from planar to tubular and then to cage-like B structures in both neutral and charged species. Half-sandwich-type structures are most favorable for small MnB n − / 0 / + ( n   ⩽  13) clusters and gradually transform to Mn-centered double-ring tubular structures at MnB 16 − / 0 / + clusters with superior thermodynamic stabilities compared with their neighbors. Most strikingly, endohedral cages become the ground-state structures for larger MnB n − / 0 / + ( n   ⩾  19) clusters, among which MnB 20 + adopts a highly symmetric structure with superior thermodynamic stability and a large HOMO-LUMO gap of 4.53 eV. The unique stability of the endohedral MnB 2 0 + cage is attributed to the geometric fit and formation of 18-electron closed-shell configuration. The results significantly advance our understanding about the structure and bonding of B-based clusters and strongly suggest transition-metal doping as a viable route to synthesize intriguing B-based nanomaterials.